SOCIAL POLITICS IN LATIN AMERICA CONCERNING GLOBAL ECONOMY - Kenia Cristina Lopes Abrao (European Scientific Journal, ESJ, 2015)
This article intends to discuss the constitution and development process of social politics in the context of Latin-American capitalist production forms, which are determined by a subordinate position towards international organizations’ guidelines, as it occurs in the Brazilian case. It is evident that the mechanisms that allow the prevalence of labor force dependency and overexploitation, present in peripheral countries, express the essential disparities of the contradiction between capital and labor and directly affect Brazilian social politics configuration.